An Overview of Nuclear Magnetic Resonance: A Review - Lalit Kumar; Anandveer Sindhu (International Journal of Engineering and Management Research, 2023)
Nuclear Magnetic Resonance (NMR) spectroscopy is the most important techniques that has been developed in the recent past decades. Matter, organic compounds and biological and non biological applications ranging from a particular cell to different organs and various tissues. has been investigated through NMR. Aspects of this technique are still under research and many functions and various applications of the NMR are still under process. This review paper is aimed at providing a general overview of the different NMR, main principles and pro and con of NMR spectroscopy. Inspite of all of these we have discussed the various use of NMR in the field of science and medicine and ongoing development of NMR spectroscopy.